COVID-19 and the Electronic Health Record: Tool Design and Evolution at the U.S. Pandemic Epicenter - Tsega, Surafel; Vijayaraghavan, Mahima; Chronister, Marianne; Srinivas, Sindhu; Bassily-Marcus, Adel; Gumprecht, Jeffrey; Shetreat-Klein, Avniel; Darrow, Bruce; Craven, Catherine K. (ACI Open, 2022)
Objective We detail inpatient electronic health record (EHR) system tools created at Mount Sinai Health System for the clinical management of patients with coronavirus disease 2019 (COVID-19) during the early pandemic months in the U.S. epicenter, New York City. We discuss how we revised these tools to create a robust Care pathway, unlike other tools reported, that helped providers care for these patients as guidelines evolved.Methods Mount Sinai Health System launched a Command Center on March 8, 2020. The Chief Medical Information Officer launched a workgroup of clinical informaticists and Epic analysts tasked with rapidly creating COVID-19-related EHR tools for the inpatient setting.Results Initial EHR tools focused on inpatient order sets for care standardization and resource utilization. In preparation for a fall 2020-winter 2021 surge, we created a clinician-facing, integrated Care pathway incorporating additional Epic System-specific tools: a Care Path, a dedicated Navigator, Summary and Timeline Reports, and SmartTexts.Discussion Initial tools offered standard functionality but included complex decision-making support to account for the lack of COVID-19 clinical knowledge, operational challenges during a dramatic patient surge, and resource limitations. We revised content and built a more comprehensive Care pathway that provided real-time clinical data along with treatment recommendations as knowledge evolved, e.g., convalescent plasma.Conclusion We have provided a framework that can inform future informaticists in developing EHR tools during an evolving pandemic.
Keywords: inpatient; order entry; specific types; clinical information systems; data visualization; general medicine admission; inpatient care; environment; clinical care